Technological Development: Key Link for National Development - Sicchar Valdez, Javier Enrique (2005)
The Peruvian State has sustained a policy of systematic abandonment of science and technology, an attitude that has relegated us to the last places in Latin America. This situation is currently aggravated by the pressure exerted by the US to modify patent regulations in its favor, which could slow down national learning processes and reduce the technological gap. In addition, transnational companies reduce the research and development actions of their local subsidiaries. A national consensus is urgently needed to establish a new institutional framework that turns research and technological innovation into the key link in the irreversible leap to development.